Awareness and Attitude Towards Periodontology as a Career among Postgraduates in Tamil Nadu - An Evaluative Study - Komal Vilas; Anilkumar Kanakamedala; Geetha Ari; Jaideep Mahendra; Sathish Rajendran; Ambalavanan Namasivayam (Indian Journal of Dental Research)
Background: Knowledge of postgraduates’ expectations of their profession as well as their attitude toward studying a particular speciality of dentistry is of great importance. These attitudes and expectations make studying dentistry meaningful to postgraduates and society and understanding these factors facilitate workforce planning in the dental sector. The aim of the study was to assess the attitude and knowledge among postgraduates of periodontology studying in Tamil Nadu toward periodontology as a future career. Materials and Methods: A questionnaire-based cross-sectional survey was conducted. A total of 175 postgraduates belonging to the third year, second year, and first year studying in 22 institutions were approached for their participation in the survey. A 10-item close-ended questionnaire was sent out electronically via Google form to postgraduates of periodontology. This study was carried between March 2022 and April 2022 and after collecting the data from the students, the statistical analysis was done, and results were obtained by using SPSS Version 16 software, and descriptive statistics were expressed as percentage of responds on selected variables. Results: A total of 164 of the 175 registered postgraduate students participated in the study, with an overall response rate of 93.7%. Among 164 respondents, 98 (59.7%) were females and 66 (40.3%) were males. Among the total sample that was studied, it was observed that only two-thirds (58.23%) of the respondents had a positive attitude toward selecting periodontology as their future career and nearly one-third of them (33.52%) had a neutral attitude, with very few students having negative attitude (8.23%) toward the speciality. Conclusion: This study found that most of postgraduates choosing periodontics as a career was because of strong interest in implantology and to improve their skills as a surgeon. There was a slighter negative impact when they were asked about fulfilling their role in future research strategy and opportunity for professional growth in the Department of Periodontology when selecting periodontics as their speciality of choice.